2005
DOI: 10.1111/j.1523-1755.2005.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus for induction therapy of diffuse proliferative lupus nephritis: An open-labeled pilot study

Abstract: Tacrolimus is an effective option for induction treatment of SLE-diffuse proliferative glomerulonephritis. Further trials are necessary to determine the optimal dosage and duration of therapy, and its efficacy in comparison to standard regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 22 publications
3
105
1
1
Order By: Relevance
“…19 Tacrolimus can suppress IL-2 transcriptions, inhibit T cell activation, 20 decrease the production of TNF-␣ and IFN-␥, 21 and inhibit IL-10 production. 19,22,23 Although Nash et al 24 reported tacrolimus to reduce the GFR, neither our study nor the reports from Mok et al 25 and Tse et al 26 observed such an effect. This may be ascribed to a relatively lower dosage adopted in these studies (approximately 0.06 to 0.10 versus approximately 0.12 to 0.15 mg/kg per d).…”
Section: Discussioncontrasting
confidence: 81%
“…19 Tacrolimus can suppress IL-2 transcriptions, inhibit T cell activation, 20 decrease the production of TNF-␣ and IFN-␥, 21 and inhibit IL-10 production. 19,22,23 Although Nash et al 24 reported tacrolimus to reduce the GFR, neither our study nor the reports from Mok et al 25 and Tse et al 26 observed such an effect. This may be ascribed to a relatively lower dosage adopted in these studies (approximately 0.06 to 0.10 versus approximately 0.12 to 0.15 mg/kg per d).…”
Section: Discussioncontrasting
confidence: 81%
“…Tacrolimus has been used with success in severe focal segmental glomerulosclerosis (6,7), resistant membranous nephropathy (8) and lupus nephritis (9). Mycophenolate mofetil has been successfully used in membranous nephropathy (10,11), resistant minimal change disease (11,12), and focal segmental glomerulosclerosis (12).…”
Section: The Choice Of Immunosuppressive Medication Used After Kidneymentioning
confidence: 99%
“…Indeed, to date several papers have described the efficacy and safety of Tac in patients with active SLE (Duddridge & Powell, 1997). Recently, Tac combined with PDN has been successfully administered without serious adverse effects, as induction and maintenance treatment for patients with proliferative and membranous lupus nephritis (Politt et al, 2004;Maruyama et al, 2005;Mok et al, 2005;Tse et al, 2007;Szeto et al, 2008). However, there is little information regarding the efficacy and safety of Tac in young patients with lupus nephritis (Tanaka et al, 2007a(Tanaka et al, , 2009).…”
Section: Tacrolimus a Calcineurin Inhibitormentioning
confidence: 99%